2002
DOI: 10.1002/jso.10145
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative morbidity, mortality, and survival in lung cancer associated with idiopathic pulmonary fibrosis

Abstract: Patients with IPF showed markedly higher postoperative pulmonary morbidity and mortality than those without IPF. The survival rate of patients with IPF was lower because of pulmonary complications. Careful preoperative evaluation and perioperative management are required to achieve optimal surgical outcome in patients with lung cancer who have IPF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 15 publications
7
62
3
Order By: Relevance
“…Previous studies [20][21][22][23][24][25] reported that postoperative respiratory complications were found in 26%-54.0% of patients with IPF, moderately higher than in the present study, in which the CPFE group had a significantly higher rate of cardiopulmonary morbidity than the IPF alone group; this was assumed to be due to the fact that postoperative PFT decreased unexpectedly in CPFE, involving both %VC and FEV1%, because the CPFE patients experienced AE at almost the same rate as IPF patients without emphysema and required more HOT than IPF patients without emphysema. Moreover, previous studies 7,9,10,14) noted that CPFE was highly associated with pulmonary hypertension, which might be regarded as a cause of more 19) reported that postoperative pulmonary complications occurred in 20% of CPFE patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [20][21][22][23][24][25] reported that postoperative respiratory complications were found in 26%-54.0% of patients with IPF, moderately higher than in the present study, in which the CPFE group had a significantly higher rate of cardiopulmonary morbidity than the IPF alone group; this was assumed to be due to the fact that postoperative PFT decreased unexpectedly in CPFE, involving both %VC and FEV1%, because the CPFE patients experienced AE at almost the same rate as IPF patients without emphysema and required more HOT than IPF patients without emphysema. Moreover, previous studies 7,9,10,14) noted that CPFE was highly associated with pulmonary hypertension, which might be regarded as a cause of more 19) reported that postoperative pulmonary complications occurred in 20% of CPFE patients.…”
Section: Discussionmentioning
confidence: 99%
“…Various researchers have reported that UIP pattern lesions are found in 12%-17% of patients undergoing lung cancer surgery, in agreement with our study. 4) Yano et al reported that the mortality rate of patients who developed the acute exacerbation of UIP pattern after surgery was 91.7%. 5) In conclusion, we report a case of acute exacerbation of IPF of microscopic UIP pattern after lung cancer surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence might be higher in Japanese patients due to greater awareness of ILD compared with the rest of the world, differences in ILD definitions or increased genetic susceptibility. In one retrospective study of 711 Japanese patients with lung cancer who had undergone surgical resection, 7.5% had idiopathic pulmonary fibrosis, a type of ILD (Kawasaki et al, 2002). Interstitial lung disease is a known complication of chemotherapy and radiotherapy in patients with lung cancer (Abid et al, 2001) and many patients with advanced NSCLC have no further treatment options, so the benefits of gefitinib treatment outweigh the risks of ILD.…”
Section: Discussionmentioning
confidence: 99%